P2.20 Male partner linkage to clinic-based sti/hiv services following a home-based couple antenatal education and testing intervention in western kenya: a randomised controlled trial. (8th July 2017) - Mark, Jennifer; J, Kinuthia; A, Osoti; D, Krakowiak; A, Roxby; Ma, Gone; V, Asila; S, Parikh; M, Sharma; Ba, Richardson; C, Farquhar
Abstract : Introduction: Offering couples education and HIV rapid testing during pregnancy can increase testing of male partners, identify sero-discordant couples, and help link men to HIV care services. We aim to understand how a home-based antenatal couple HIV testing intervention affects male partner follow-up to clinic-based STI services during pregnancy. Methods: We conducted a randomised controlled trial of un-accompanied pregnant women attending a first visit at Kisumu County Hospital from September 2013 to June 2014. Women and their partners received either home-based couple education with HIV and syphilis testing during pregnancy or an invitation letter to clinic-based couple HIV testing. Men's self-reported health seeking outcomes during pregnancy were compared at 6 months postpartum. Results: Among 601 enrolled women, we reached 247 and 240 men in the intervention and control arms, respectively (85% participation). Men who received the intervention were more likely to seek an STI consultation based on symptoms or a positive syphilis test [RR=1.59; 95%CI=1.33–1.89]. Postpartum, 39 (16%) intervention and 21 (9%) control men reported known HIV-positive status during pregnancy. Despite increased knowledge of HIV-positive status within the intervention group, men were less likely to link to HIV care services [RR=0.69; 95%CI=0.50–0.96], as 41% (16 of 39) of men were newly diagnosed with HIV. No differences were observed for uptake of male circumcision within the study period [RR=1.59; 95%CI=0.89–2.87] or attendance of subsequent clinic-based antenatal care with the female partner [RR=1.11; 95%CI=0.85–1.41]. Conclusion: Home-based couple education and testing resulted in greater uptake of clinic-based STI consultation services among men. However, increased knowledge of HIV-status in the home did not lead to increased HIV care service uptake for men, potentially because there was a greater proportion of men with new HIV diagnoses in the intervention arm. This group of newly diagnosed men should be targeted with research to increase linkage and engagement to HIV care.